The taphonomy of dinosaurs from the Upper Jurassic of Tendaguru (Tanzania) based on field sketches of the German tendaguru expedition (1909–1913) - W.-D. Heinrich (Fossil Record, 1999)
Tendaguru is one of the most important dinosaur localities in Africa. The Tendaguru Beds have produced a diverse Late Jurassic (Kimmeridgian to Tithonian) dinosaur assemblage, including sauropods (Brachiosaurus, Barosaurus, Dicraeosaurus, Janenschia), theropods (e.g., Elaphrosaurus, Ceratosaurus, Allosaurus), and ornithischians (Kentrosaurus, Dryosaurus). Contrary to the well studied skeletal anatomy of the Tendaguru dinosaurs, the available taphonomic information is rather limited, and a generally accepted taphonomic model has not yet been established. Assessment of unpublished excavation sketches by the German Tendaguru expedition (1909–1913) document bone assemblages of sauropod and ornithischian dinosaurs from the Middle Saurian Bed, Upper Saurian Bed, and the Transitional Sands above the Trigonia smeei Bed, and shed some light on the taphonomy of the Tendaguru dinosaurs. Stages of disarticulation range from incomplete skeletons to solitary bones, and strongly argue for carcass decay and post-mortem transport prior to burial. The sauropod bone accumulations are dominated by adult individuals, and juveniles are rare or missing. The occurrence of bones in different superimposed dinosaur-bearing horizons indicates that skeletal remains were accumulated over a long time span during the Late Jurassic, and the majority of the bone accumulations are probably attritional. These accumulations are likely to have resulted from long-term bone imput due to normal mortality events caused by starvation, seasonal drought, disease, old age and weakness. The depositional environment of the Middle and Upper Saurian Bed was mainly limnic to brackish in origin, while the palaeoenvironment of the Transitional Sands was marginal marine. Tendaguru zählt zu den bedeutendsten Dinosaurier-Lagerstätten Afrikas. Aus den Tendaguru-Schichten sind zahlreiche Skelettreste von Sauropoden (Brachiosaurus, Barosaurus, Dicraeosaurus, Janenschia), Theropoden (z.B. Elaphrosaurus, Ceratosaurus, Allosaurus) und Ornithischiern (Kentrosaurus, Dryosaurus) geborgen worden. Sie stammen aus der späten Jura-Zeit (Kimmeridge — Tithon). Während der Skelettbau der Tendagurusaurier gut untersucht ist, wirft die Taphonomie des Sauriervorkommens von Tendaguru noch immer Fragen auf. Unklar ist bislang, wie die enormen Anreicherungen von Dinosaurierknochen in den Tendaguru-Schichten zustandekamen. Unveröffentlichte Grabungsskizzen der Deutschen Tendaguru Expedition (1909–1913) erweitern unsere Kenntnisse über die Taphonomie der Tendagurusaurier. In den ausgewerteten Grabungsskizzen sind Knochenansammlungen von Sauropoden und Ornithischiern aus dem Mittleren und Oberen Sauriermergel sowie aus den Übergangsschichten über der Trigonia smeei-Schicht dokumentiert. Die Lage und der Erhaltungszustand der Funde lassen auf erheblichen Zerfall der Kadaver und post-mortalen Transport von Skelettelementen vor der Einbettung schließen. Das Vorkommen von Saurierknochen in mehreren übereinanderliegenden Profilabschnitten der Tendaguru-Schichten zeigt, daß Skelettreste während der späten Jura-Zeit über einen längeren Zeitraum hinweg akkumuliert wurden. Die Ansammlungen von Skelettresten gehen wahrscheinlich auf „normale” Sterbe-Ereignisse zurück, wie z. B. Verhungern, Verdursten, Kankheit, Altersschwäche und jahreszeitliche Dürre. Als Ablagerungsraum der Mittleren und Oberen Saurierschicht kommt ein küstennaher limnischer, zeitweise wohl auch brackischer Küstenstreifen in Betracht. Die knochenführenden Übergangsschichten unter- und oberhalb der Saurierschichten sind randlich marine Ablagerungen. doi:10.1002/mmng.1999.4860020102